(untitled) (Journal of Parents and Teachers, 2025)
The article centers on a conversation between a mother and her children regarding the news about the separation of sexes in schools. The children want to be together in classrooms, mixed and intertwined, as a way to learn what real life is about—avoiding segregation and fostering camaraderie among everyone. Additionally, throughout the article, questions are addressed such as: Coexistence or living together?, Brains or people? and ideas for addressing sexism in the classroom.